Analysis of mechanical behavior of implant-supported prostheses in the anterior maxilla: analysis by speckle pattern interferometry - Correa, Cassia B. [UNESP]; Ramos, Nuno V.; Monteiro, Jaime; Vaz, Luis Geraldo [UNESP]; Vaz, Mario A. P. (Spie - Int Soc Optical Engineering, 2012)
The use of implants to rehabilitation of total edentulous, partial edentulous or single tooth is increasing, it is due to the high rate of success that this type of treatment present. The objective of this study was to analyze the mechanical behavior of different positions of two dental implants in a rehabilitation of 4 teeth in the region of maxilla anterior. The groups studied were divided according the positioning of the implants. The Group 1: Internal Hexagonal implant in position of lateral incisors and pontic in region of central incisors; Group 2: Internal Hexagonal implant in position of central incisors and cantilever of the lateral incisors and Group3 - : Internal Hexagonal implants alternate with suspended elements. The Electronic Speckle Pattern Interferometry (ESPI) technique was selected for the mechanical evaluation of the 3 groups performance. The results are shown in interferometric phase maps representing the displacement field of the prosthetic structure.
Keywords: Biomechanics; Prostheses and Implants